Schistosomes induce regulatory features in human and mouse CD1d(hi) B cells: inhibition of allergic inflammation by IL-10 and regulatory T cells - van der Vlugt, Luciën E P M; Labuda, Lucja A; Ozir-Fazalalikhan, Arifa; Lievers, Ellen; Gloudemans, Anouk K; Liu, Kit-Yeng; Barr, Tom A; Sparwasser, Tim; Boon, Louis; Ngoa, Ulysse Ateba; Feugap, Eliane Ngoune; Adegnika, Ayola A; et al. (PloS one, 2012)
Chronic helminth infections, such as schistosomes, are negatively associated with allergic disorders. Here, using B cell IL-10-deficient mice, Schistosoma mansoni-mediated protection against experimental ovalbumin-induced allergic airway inflammation (AAI) was shown to be specifically dependent on IL-10-producing B cells. To study the organs involved, we transferred B cells from lungs, mesenteric lymph nodes or spleen of OVA-infected mice to recipient OVA-sensitized mice, and showed that both lung and splenic B cells reduced AAI, but only splenic B cells in an IL-10-dependent manner. Although splenic B cell protection was accompanied by elevated levels of pulmonary FoxP3(+) regulatory T cells, in vivo ablation of FoxP3(+) T cells only moderately restored AAI, indicating an important role for the direct suppressory effect of regulatory B cells. Splenic marginal zone CD1d(+) B cells proved to be the responsible splenic B cell subset as they produced high levels of IL-10 and induced FoxP3(+) T cells in vitro. Indeed, transfer of CD1d(+) MZ-depleted splenic B cells from infected mice restored AAI. Markedly, we found a similarly elevated population of CD1d(hi) B cells in peripheral blood of Schistosoma haematobium-infected Gabonese children compared to uninfected children and these cells produced elevated levels of IL-10. Importantly, the number of IL-10-producing CD1d(hi) B cells was reduced after anti-schistosome treatment. This study points out that in both mice and men schistosomes have the capacity to drive the development of IL-10-producing regulatory CD1d(hi) B cells and furthermore, these are instrumental in reducing experimental allergic inflammation in mice.